Tinjauan Hukum Islam Terhadap Tradisi Ngemblok Dalam Prosesi Lamaran : (Studi Kasus Desa Katerban, Tuban) - Nisyatun Nasayatin Nafi’ah; Abdullah Afif (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Sub-District of Senori, Tuban Regency. Generally, the proposal (marriage proposal) that takes place in the village involves men proposing to women, different from that of the village where a woman takes the role as the proposer. This marriage proposal activity conducted by women is called "ngemblok". The tradition of ngemblok is one of the cultural heritages passed down from ancestors. The research method used by the researcher is qualitative research with field research as its type. The results of this research show that: 1) the implementation of the ngemblok tradition in the marriage proposal process in Katerban Village, Senori Sub-District, Tuban Regency, consists of several stages starting from bringing offerings such as tape (fermented cassava), bugisan (a type of traditional cake), rengginang (rice crackers), jenang (a type of sweet food), and mandatory alu-alu (traditional grinding stone) as symbolic food. 2) The Islamic legal perspective on the ngemblok tradition states that there is no prohibition for women as proposers. Through the approach of the 'urf theory